Redrawing the Red Line : Researching Possibilities of International Law to Secure Accountability for the Use of Chemical Weapons in Syria Through Individual Criminal Responsibility - Veini, Sannimari (My University, 2021)
The topic of this research is the use of chemical weapons (CW) in the Syrian Civil War, and it studies their prohibition in international law, different channels for individual criminal responsibility, and different efforts taken to contribute to the accountability within the Syrian context. In addition, through problem-oriented case analysis, this research analyses where the most significant issues in holding perpetrators of the CW attacks accountable are located by comparing the regulatory framework to the actions taken in Syria. Finally, based on the analysis's outcome, this research considers how well-adapted the current system is to hold perpetrators of CW attacks accountable and further, how the system could be strengthened. Sources of this research include, most importantly, diverse legal literature, documents of the United Nations, and international treaties, especially the Rome Statute of the International Criminal Court. In addition, especially to map the situation and actions taken in Syria, a wide range of different news sources and reports are utilized. To form a basis for the analysis, this research briefly introduces the events relating to CWs during the Syrian Civil War (chapter 2) and studies their regulation and avenues for accountability under international law (chapter 3). After this, actual actions taken by different actors in Syria are introduced and compared to the existing regulatory framework (chapter 4). The comparison is then used as a starting point for further analysis of obstacles to international accountability (chapter 5). Finally, development possibilities based on the pointed problems are considered (chapter 6). This research concludes that the prohibition of the use of CW has a solid base in international law and that several avenues for accountability exist, but in the case of Syria, severe gaps in accountability remain. Based on the analyze this research considers that the biggest obstacles for accountability include the distribution of responsibilities in the UN, the role and veto power of the UNSC, state sovereignty, and relating to the principle of universal jurisdiction: the unclarity of its scope and lack of a venue for its effective enforcement. Based on these considerations, suggestions to strengthen the system include: reorganizing the UN, enhancing the R2P doctrine, clarifying the scope of the universal jurisdiction, and considering an independent body for its implementation, as well as utilizing the framework of the CWC.

Työn aiheena on kemiallisten aseiden käyttö Syyrian sisällissodassa ja se tutkii, miten niiden käyttöä säännellään kansainvälisessä oikeudessa, minkä kanavien kautta rikosoikeudellinen vastuu voidaan toteuttaa ja millaisiin keinoihin Syyrian suhteen on ryhdytty kemiallisiin iskuihin syyllisten vastuuseen saattamiseksi. Ongelmakeskeisen tapaustutkimuksen kautta työ analysoi, mitkä ovat järjestelmän keskeisimpiä ongelmia vertailemalla olemassa olevaa sääntelyä Syyriassa käytettyihin keinoihin ja aitoihin mahdollisuuksiin. Analyysin perusteella punnitaan, kuinka hyvin nykyinen sääntely soveltuu saattamaan kemiallisten aseiden käyttäjät vastuuseen kansainvälisellä tasolla ja miten sääntely-ympäristöä olisi mahdollista kehittää. Työn keskeisimpiin lähteisiin lukeutuu laajasti erilaista oikeuskirjallisuutta, YK:n asiakirjoja sekä kansainvälisiä sopimuksia, joista Kansainvälisen rikostuomioistuimen Rooman perussääntöön on kiinnitetty erityistä huomiota. Syyrian tapahtumien selvittämiseksi myös erilaisia uutislähteitä ja raportteja on hyödynnetty laajasti. Ensin työ kuvaa lyhyesti kemiallisiin aseisiin liittyviä vaiheita Syyrian konfliktissa (kappale 2), jonka jälkeen se selvittää millaista kemiallisten aseiden sääntely on ja miten rikosoikeudellinen vastuu voidaan kansainvälisessä ympäristössä toteuttaa (kappale 3). Kappaleessa 4 työ keskittyy erilaisiin toimiin, joihin kemiallisten aseiden käytön vuoksi on Syyrian tapauksessa ryhdytty, ja vertailee näitä keinoja sääntelyn tarjoamiin mahdollisuuksiin. Vertailun pohjalta kappaleessa 5 analysoidaan nykyisen järjestelmän suurimpia haasteita käytännön tilanteessa. Lopuksi esitetään joitakin kehitysedotuksia kappaleen 5 pohdintoihin perustuen. Tutkimus osoittaa, että kemiallisten aseiden kielto on kansainvälisessä järjestelmässä vahva ja että järjestelmä tarjoaa erilaisia reittejä rikosoikeudelliselle vastuulle, mutta ainakin Syyrian tilanteessa, järjestelmässä on vakavia aukkoja. Analyysin pohjalta tutkimus tulee tulokseen, että suurimmat ongelmat nykyisessä järjestelmässä ovat vastuunjako YK:n eri toimijoiden välillä, erityisesti turvallisuusneuvoston rooli, valtioiden suvereniteetti, sekä universaaliperiaatteen näkökulmasta sen sisällön epäselvyys ja tehokkuuden puute. Näiden ongelmien valossa esitetään, että systeemiä olisi mahdollista vahvistaa YK:n uudelleenjärjestelyllä, vahvistamalla suojeluvastuun doktriinia, selkeyttämällä universaaliperiaatteen sisältöä ja punnitsemalla mahdollisuutta periaatteen toimeenpanoa vahvistavalle toimijalle, sekä hyödyntämällä kemiallisten aseiden kieltosopimuksen tarjoamia mahdollisuuksia.
Keywords: International criminal law, chemical weapons, Syrian Civil War, international courts, jurisdiction, accountability, war crimes